Descent methods with computational errors in Banach spaces. (2nd August 2020) - Reich, Simeon; Zaslavski, Alexander J.
ABSTRACT: Given a Lipschitz convex and coercive objective function on a Banach space, we revisit the class of regular vector fields introduced in our previous work on descent methods. Taking into account computational errors, we study the behaviour of the values of the objective function for the process generated by a regular vector field and show that if the computational errors are small enough, then the values of the objective function become close to its infimum.